SOCIAL AND CULTURAL BASIS IN EDUCATION - Munawaroh Munawaroh; Muhammad Rafii; Defita Permata Sari (IAIN Padangsidimpuan, 2022)
This article seeks to explain the social and cultural foundations in the provision of education. Teachers in the learning process are emphasized to understand the social and cultural foundations in interacting with students. However, this has not been implemented optimally at every level of education. On that basis, this research was conducted to reinforce and reconstruct the socio-cultural foundation and its function in the educational process, because of the importance of knowledge and understanding of the socio-cultural aspects of learning. This research uses literature study to obtain information from various sources: books, research reports, and scientific articles that are relevant to the research topic. The results of this study indicate that the social and cultural foundation is the basic foundation that must be understood by every educator and education provider in order to realize learning in accordance with the socio-cultural context of the Indonesian people. The function of the socio-cultural foundation is as a preserver of national and local culture as well as instilling virtue values so that it can form students with character. Thus, it is clear the importance of social and cultural aspects as a foundation in education for both leaders of educational institutions and teaching staff.